Pendampingan Penyusunan Proposal Program Kreativitas Mahasiswa (PKM) Prodi Manajemen Sekolah Tinggi Ilmu Ekonomi Bima - Puji Muniarty; M Rimawan; Ovriyadin Ovriyadin; Wulandari Wulandari; Tri Wahyuni Alifah; Salimatul Uyun; Gunawan Sakti (Pakis Journal Institute, 2024)
The PKM program is a routine grant program every year which will be participated in by PTN and PTS which is organized by the Belmawa Directorate as a forum for channeling student creative ideas. The hope is that by launching the Student Creativity Program (PKM) in various fields, it will train students to be able to present solutions to problems faced by the government, society, or the world of work/industry, so that the life of the nation and state moves in a better direction. The participation of students and accompanying lecturers in PKM activities can support the achievement of their higher education's IKU. Especially at IKU 1 (graduates get decent work), IKU 2 (students get experience outside campus), IKU 3 (lecturers carry out activities outside campus), and IKU 5 (the results of lecturers' work are used by the community). Apart from that, the output of this PKM program can be in the form of articles that are declared to have passed by reviewers and can be published in a scientific journal, which is a form of dissemination of activities carried out by students and indirectly contributes to progress and technology. However, the problem in 2024 is that there is still low student participation in taking part in PKM grants and low knowledge and understanding of students in preparing proposals and taking part in PKM and difficulty finding ideas to put into writing. The community service method uses a participatory method through a preliminary stage, core stage and advanced stage. The results of the activity show that it was carried out according to the timeline and increased student interest in developing ideas and skills as well as student interest in proposing PKM, this is proven by the increase in the number of PKM proposals proposed in the Simbelmawa system.